MENGUBAH PROFESI, MENGUBAH DUNIA : Yesus Memanggil Murid-MuridNya yang pertama (Mat. 4:18-22) - Edwar Adelbert Mere (Pineleng Theological Review, 2026)
This study analyzes the text of Matthew 4:18–22 regarding the calling of the first disciples at the Sea of Galilee as a crucial moment in the formation of Jesus' mission community. The purpose of this writing is to explore deep meaning through textual, narrative, and various multidimensional approaches to find theological relevance for contemporary life. Textually, the emphasis is placed on the use of the term "immediately" and the metaphor "fishers of men," which demonstrate the sovereignty of Jesus and the transformation of a humble profession into a radical spiritual mission. From a narrative perspective, the disciples' act of leaving their nets and families reflects a severance of social and economic contracts for the sake of total obedience to the Teacher. Through social and historical approaches, it is evident how Jesus formed a new community amidst the political pressures of Herod Antipas and the Roman taxation system. Theological and psychological analyses show that the divine initiative transcends human logic, creating instantaneous obedience through the power of the Word. Finally, this text serves as a foundation for the doctrine of discipleship in the Church, asserting that following Christ requires a detachment from old identities in order to adopt a life orientation centered on the salvation of others within the Kingdom of God.